Nachhaltiges Landmanagement, differenzierte Landnutzung und Klimaschutz. - Haber, Wolfgang; Bückmann, Walter (My University, 2013)
Nachhaltiges Landmanagement umfasst die Erhaltung oder Wiederherstellung von Landflächen, Böden und Gewässern und der damit zusammenhängenden natürlichen Ressourcen. Seine Verwirklichung erfordert eine differenzierte Landnutzung, die außer der Biodiversität auch die unbelebte Natur mit Klima, Relief und Gewässern sowie die strukturelle Vielfalt der Landschaft einbezieht, und vor allem den Bodenschutz dient. Da solches Landmanagement auch die durch Landnutzungen bedingten Treibhausgasemissionen steuert, hängt es eng mit dem Klimaschutz zusammen, zumal dieser mit der Umstellung auf erneuerbare Energien selbst große Landnutzungsänderungen veranlasst.

Sustainable land management implies conservation or restoration of land, soils and water bodies, together with all natural resources they embrace. Its implementation requires a differentiated land use that takes into account, besides biodiversity, all components of non-living nature like climate, terrain and water as well as landscape structures, with a focus on soil conservation. As such land management will also control greenhouse gas emissions resulting from land use; it is closely connected with climate protection which in its turn is causing large-scale land use changes through the conversion to renewable energies. Linking land management and climate protection within the scope of sustainable development opens the way towards a comprehensive earth-system approach avoiding biased views, allowing improved assessments of time dimensions, and thus will counteract the depletion of the earth s matter and energy resources.
Sustainable Landmanagement, differential land use and climate protection.
Keywords: Landschaft; Flächennutzung; Bodennutzung; Nutzungskonflikt; Landschaftsschutz; Naturschutz; Klima; Ressourcen; Flächenmanagement; Landmanagement; Nachhaltigkeit; Klimaschutz